2021
DOI: 10.1590/1413-7054202145007021
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid relieves the effect of saline stress on soursop morphysiology

Abstract: The cultivation of soursop has increased in recent years due to the advance of agribusiness and due to its use by the pharmaceutical industry. As a source of vitamin C, calcium, carbohydrates and antioxidant substances, soursop helps to protect the human body against oxidative stress, acting in the prevention of a series of chronic degenerative disorders. In this context, the objective of present study was to evaluate the effects of foliar sprays with salicylic acid to mitigate the effects of salt stress on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…Similar results were obtained in a study conducted by Silva et al (2021a), who evaluated the effect of salt stress caused by irrigation water (0.8 to 4.0 dS m -1 ) on soursop morphophysiology at 480 days after transplanting and found that irrigation with ECw above 1.7 dS m -1 reduced soursop growth, with the lowest values of SD (30.09 mm) and VVI (2.42) obtained in plants subjected to ECw of 4.0 dS m -1 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were obtained in a study conducted by Silva et al (2021a), who evaluated the effect of salt stress caused by irrigation water (0.8 to 4.0 dS m -1 ) on soursop morphophysiology at 480 days after transplanting and found that irrigation with ECw above 1.7 dS m -1 reduced soursop growth, with the lowest values of SD (30.09 mm) and VVI (2.42) obtained in plants subjected to ECw of 4.0 dS m -1 .…”
Section: Resultssupporting
confidence: 91%
“…The increase in the percentage of electrolyte leakage and water saturation deficit in plants subjected to higher H 2 O 2 concentration (30 μM) may occur because, at high concentration, hydrogen peroxide can intensify the deleterious effects of salt stress, causing changes in plant metabolism due to the restriction of photosynthetic processes. Under salt stress conditions, photosynthetic processes can be affected directly, by stomatal restriction, reduced transpiration, and consequently, low CO 2 availability, or indirectly, by the imbalance between the production and removal of reactive oxygen species (ROS) produced during the photosynthetic process, causing oxidative stress (Carvalho et al, 2011;Silva et al, 2021a).…”
Section: Resultsmentioning
confidence: 99%
“…Em outra pesquisa, Silva et al (2021b) ratificaram os efeitos do ácido salicílico (AS) na mitigação do estresse salino na morfofisiologia da gravioleira, ao confirmarem a atenuação dos efeitos da água de irrigação com CE de1,6; 2,4; 3,2 e 4,0 dS m -1 sobre a condutância estomática, a taxa de assimilação de CO2, a transpiração e a eficiência instantânea da carboxilação da gravioleira após a aplicação foliar de AS entre as concentrações de 1,2 e 1,6 mM. Veloso et al (2019) avaliaram os efeitos da aplicação exógena de quatro concentrações de peróxido de hidrogênio -H2O2 (0, 25, 50 e 75 µM) sobre o crescimento da gravioleira 'Morada Nova' irrigada com água de condutividade elétrica 0,7; 1,7; 2,7 e 3,7 dS m -1 .…”
Section: Simões Et Al (unclassified
“…Thus, studies that enable the use of saline waters in irrigated agriculture are important to ensure the sustainability of crops. In this context, the use of salicylic acid has emerged as a promising alternative for minimizing the deleterious effects caused by salt stress on plants [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that foliar spraying with salicylic acid can attenuate the deleterious effects caused by salt stress in strawberry [ 23 ], American grapevine [ 24 ], date palm [ 25 ], orange [ 26 ], and soursop [ 18 ]. However, information on its use in sour passion fruit crops irrigated with saline water is incipient in the literature.…”
Section: Introductionmentioning
confidence: 99%